The burden of diarrhea in the intensive care unit (ICU-BD). A survey and observational study of the caregivers' opinions and workload. (July 2016) - Heidegger, Claudia-Paula; Graf, Séverine; Perneger, Thomas; Genton, Laurence; Oshima, Taku; Pichard, Claude
Abstract: Background: Diarrhea as a common complication affects 14% patients in our intensive care unit. Risk factors for diarrhea and its clinical consequences for patients are well known, but the impact of diarrhea on caregivers' workload remains undocumented. Objectives: This study aims at establishing the impact of diarrhea on costs and human burden in intensive care unit caregivers. Design: A survey and observational study. Settings: A mixed 36-bed medical and surgical intensive care unit. Participants: All intensive care unit caregivers (nurses and nursing aides). Methods: A questionnaire was designed by a multidisciplinary team and completed by intensive care unit caregivers analyzing the clinical and human impact of diarrhea on their workload. Time measurements for the management of liquid stools were performed. Human related costs of diarrhea were analyzed according to caregivers' years of clinical experience. Results: Questionnaires were completed by 146 of 204 intensive care unit caregivers (75% nurses; 73% nursing aides). Dealing with diarrhea patients is a painful aspect of their work (69% nurses) with tiredness as main feeling and a source of conflict or misunderstanding among caregivers. The mean time measurement for managing one liquid stool in 50 diarrhea episodes was 17 min and 33 s, involving an average of 1.4 nurses and 0.8 nursing aides. Average human resources cost burden was 26.60 CHF per liquid stool. Conclusion: Dealing with diarrhea increases workload for intensive care unit caregivers with consequences on their well-being. Human related costs of diarrhea are substantial and highlight the economic burden of diarrhea episodes in the intensive care unit. A multidisciplinary approach and specific protocols could positively impact the burden of diarrhea in the intensive care unit. Trial registration: Clinical Trials govNCT01922570 .